Research on the Collaborative Application of BIM in EPC Projects: The Perspective of Cooperation between Owners and General Contractors - Chengshuang Sun; Min Wang; Fengyong Zhai (Advances in Civil Engineering)
As an effective way to reduce costs and increase efficiency of EPC projects, BIM technology has drawn a lot of attention in numerous countries. Existing studies have failed to reveal the BIM decision-making mechanisms of owners and general contractors in EPC projects in a dynamic method. This study investigates the underlying logic of the collaboration application of BIM by analyzing the dynamic behaviors of owners and general contractors based on evolutionary game model. The results show that the most effective suggestions to promote the BIM collaboration application in EPC projects are “increasing the proportion of BIM application initially strategies,” “increasing incremental revenue of BIM collaborative application,” “reducing costs of BIM collaboration application,” “avoiding excessive hitchhiking,” and “establishing reasonable reward and punishment mechanism.” On the basis of numerical simulation to illustrate the influence of the different initial strategies and parameters on the final decision in different situations, five solutions were proposed for the effective BIM collaboration application between owners and general contractors. This article can facilitate researchers pondering the dynamics of collaboration among stakeholders in projects, and it can also facilitate participants picking up proper strategies for improved collaboration.